Impact of Production Technologies on Area and Productivity of Cashew in North Kerala - M.V. Sajeev, P.L. Saroj; Meera Manjusha A.V. (Indian Journal of Extension Education, 2018)
The study analyses the impact of production technologies on area, production and productivity of cashew in the Kannur and Kasaragod districts of Kerala state, as a prerequisite for developing and initiating innovative technology interventions for combating low productivity and profitability from cashew cultivation. Results revealed that highest area under cashew in farmer fields is occupied by the variety Priyanka followed by Madakkathara-2 with similar trend in adoption levels. The ‘Priyanka + Madakkathara - 2’ combination emerged to be the most popular one among farmers in the study area. Farmers realized highest production and productivity from variety Sulabha, followed by Madakkathara-2 and Priyanka. Correlation analysis showed that four technologies; recommended varieties, planting and initial care, pruning and training and plant protection as having highly significant relationship with the cashew productivity achieved by farmers. The regression analysis identified that increasing adoption of planting and initial care techniques, manures and fertilizers and development and popularization of user friendly plant protection measures can significantly increase the per unit productivity of cashew orchards in north Kerala. The study concludes that socio-economic and biophysical factors along with policy environment have a larger contribution in explaining cashew productivity and technology component alone cannot be expected to bring a positive impact. Understanding the above dynamics in technology impact can help researchers and extension agencies working in cashew sector to design better innovations and effective outreach strategies.